2014
DOI: 10.1021/jm401279n
|View full text |Cite
|
Sign up to set email alerts
|

Structure–Activity Relationships for Withanolides as Inducers of the Cellular Heat-Shock Response

Abstract: To understand the relationship between the structure and the remarkably diverse bioactivities reported for withanolides, we obtained withaferin A (WA; 1) and 36 analogues (2-37) and compared their cytotoxicity to cytoprotective heat-shock-inducing activity (HSA). By analyzing structure-activity relationships for the series, we found that the ring A enone is essential for both bioactivities. Acetylation of 27-OH of 4-epi-WA (28) to 33 enhanced both activities, whereas introduction of β-OH to WA at C-12 (29) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
113
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(122 citation statements)
references
References 50 publications
9
113
0
Order By: Relevance
“…derivatives shown in Ref. 37) will help elucidate the chemical mechanism of how WA is able to modify NEMO and alter its ubiquitin binding properties. These studies along with further ZF domain analysis could reveal a way to target only NEMO in a complex mixture of cellular environment and allow for improved drug development of this potentially novel class of ubiquitin binding modifiers.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…derivatives shown in Ref. 37) will help elucidate the chemical mechanism of how WA is able to modify NEMO and alter its ubiquitin binding properties. These studies along with further ZF domain analysis could reveal a way to target only NEMO in a complex mixture of cellular environment and allow for improved drug development of this potentially novel class of ubiquitin binding modifiers.…”
Section: Discussionmentioning
confidence: 98%
“…Interestingly, NEMO ZF contains two consecutive cysteine residues (Cys-396 and Cys-397) that are missing in all other known UBD ZF domains, including those of TAB2/3. Several chemical studies have implicated the 2(3)-en-1-one moiety in the unsaturated A-ring at the 3rd carbon position as the major reactive group on WA (37). Moreover, WA has been shown to covalently modify cysteine residues of other molecules (30, 31) most likely through this chemical group.…”
Section: Discussionmentioning
confidence: 99%
“…This proves withanolide's antiproliferative activity in treating cancer. A similar study was conducted by Wijeratne et al (2014) and found WA along with its 36 analogues for their cytotoxic potential for cytoprotective heat shock-inducing activity (HSA). Some analogues were produced by acetylation of 27-OH 4-epi-WA and some were due to introduction of b-OH to WA at C-12 and C-15 position.…”
Section: Other Withanolidesmentioning
confidence: 62%
“…Further, 2,3-dihydrowithaferin A-3β-O W. frutescens sulfate was also isolated from with undefined stereochemistry at C-3 position. These three novel withanolides possess significant cytotoxicity (0.54, 0.61 and 5.25 µM respectively) against human Ewing's sarcoma cell line CHP-100 (Wijeratne et al, 2014). Hence, It's provides a new idea to phytochemists in search of the new withanolides from W. somnifera.…”
Section: Micropropagation Of Withania Somniferamentioning
confidence: 99%